Design and Performance Analysis of Microstrip Patch Antenna Arrays for High-Speed Wireless Communication - Kumar, Kuldip; Kocher, Geeta (2025 International Conference on Electronics, AI and Computing (EAIC), 2025)
Microstrip patch antenna arrays are widely used in wireless communication systems to boost the performance of the antenna, including increasing directivity, gain, and beam scanning. The design and modeling of microstrip patch antenna arrays have been the subject of several scholarly articles. The various types of shapes of microstrip patch antenna are proposed in literature. The aim of this paper is to design an array antenna for wireless communication. This research tackles the practical difficulties involved in implementing microstrip patch antenna arrays in wireless communication systems in addition to making a contribution to the progress of the technology. The CST microwave studio tool is used for simulation of antenna. It is expected that the results would find wide uses in many wireless communication scenarios, such as point-to-point, satellite, and wireless network communication.